2016
DOI: 10.1055/s-0042-116159
|View full text |Cite
|
Sign up to set email alerts
|

Crocus sativus L. versus Citalopram in the Treatment of Major Depressive Disorder with Anxious Distress: A Double-Blind, Controlled Clinical Trial

Abstract: Saffron (.) has demonstrated antidepressant effects in clinical studies and extensive anxiolytic effects in experimental animal models. 66 patients with major depressive disorder accompanied by anxious distress were randomly assigned to receive either saffron (30 mg/day) or citalopram (40 mg/day) for 6 weeks. Hamilton Rating Scale for Depression (HAM-D) and Hamilton Rating Scale for Anxiety (HAM-A) were used to assess treatment effect during the trial. 60 participants finished the study. Patients who received … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
40
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(49 citation statements)
references
References 65 publications
2
40
0
5
Order By: Relevance
“…Consequently, we considered these two papers as one RCT. Therefore, a total of 11 placebocontrolled, randomized trials with 531 patients were included in the qualitative analysis [21][22][23][24][25][26][27][28][29][30][31][32].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, we considered these two papers as one RCT. Therefore, a total of 11 placebocontrolled, randomized trials with 531 patients were included in the qualitative analysis [21][22][23][24][25][26][27][28][29][30][31][32].…”
Section: Resultsmentioning
confidence: 99%
“…Altogether, ten articles reporting on nine trials were included in our final quantitative analysis [21][22][23][24][25][26][27][29][30][31]. Akhondzadeh et al [32] provided the baseline HAM-D scores numerically, but the outcomes were shown only graphically in a figure, therefore, we could not include the results of this trial in the quantitative analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently you published a comparison of crocus sativus vs. citalopram [1]. This paper concludes that crocus is as effective as citalopram in the treatment of mild to moderate depression.…”
Section: Sirmentioning
confidence: 88%
“…Recently, a letter to the editor entitled "Is really crocus sativus as effective as citalopram in the treatment of depression?" has concerned our investigation about safety and efficacy of Crocus sativus L. (saffron) in the treatment of mild to moderate depression [1]. The present study fulfilled all the characteristics of a typical randomized controlled trial, including the randomized allocation of interventions to the trial arms, and blinding of the patients and investigators [2].…”
mentioning
confidence: 91%